Mengukur Potensi Bahaya dan Resiko Kecelakaan Kerja dengan Metode Hazard and Operabillity Study pada Aktivitas Maintenance - Dede; Winarno (Jurnal Sistem Teknik Industri, 2021)
Work accidents are things that must be avoided, so that's not inflicted loss on the company and the workers. However, several workers still not pay attention to occupational health and safety regulations and in the work area still found several potential hazards. The research is conducted at PT Pindo Deli Pulp and Paper Mills Indonesia in Karawang Regency and focuses on preventive and corrective maintenance activities that prevent paper machine breakdown. The purpose of this study is to measure how big the potential hazard and impact by using Hazard and Operability Study (HAZOP) method. This method is a systematic study, which aims to find the factors that causing work accidents and find out how big the potential accidents and their impacts. The data is collected by distributing questionnaires to the employee. The results show that hazards caused by the work area and the workers themselves are 18% and 82%, respectively. Based on the severity, the number of extreme, high, medium and low risk hazards are 1, 8, 1 and 1, respectively.